Ownership and control in a competitive industry - Heiko Karle; Tobias J. Klein; Konrad O. Stahl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We study a differentiated product market in which an investor initially owns a controlling stake in one of two competing firms and may acquire a non-controlling or a controlling stake in a competitor, either directly using her own assets, or indirectly via the controlled firm. While industry profits are maximized within a symmetric two product monopoly, the investor attains this only in exceptional cases. Instead, she sometimes acquires a noncontrolling stake. Or she invests asymmetrically rather than pursuing a full takeover if she acquires a controlling one. Generally, she invests indirectly if she only wants to affect the product market outcome, and directly if acquiring shares is profitable per se.
Keywords: L13; L41; 330; differentiated products; separation of ownership and control; private benefits of control; Investition; Produktdifferenzierung; Corporate Governance; Unvollkommener Markt; Theorie